2004
DOI: 10.1002/ijc.20631
|View full text |Cite
|
Sign up to set email alerts
|

Reduced metastasis of transgenic mammary cancer in urokinase-deficient mice

Abstract: A prominent phenotype of plasmin deficiency in mice is reduced metastasis in the MMTV-PymT transgenic breast cancer model. Proteolytically active plasmin is generated from inactive plasminogen by one of 2 activators, uPA or tPA. We now find that uPA deficiency alone significantly reduces metastasis >7-fold in the MMTV-PymT model. We studied a cohort of 55 MMTV-PymT transgenic mice, either uPA-deficient or wild-type controls. Tumor incidence, latency, growth rate and final primary tumor burden were not signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 52 publications
10
116
1
2
Order By: Relevance
“…Lymphangiogenesis in the ovary is dependent on ADAMTS1 activity, 3,43 and in breast cancers enhanced lymphangiogenesis provides a route for dissemination to lymph nodes and eventually metastasis to distal tissues such as lung. 44 Although we found the lowest proportion of lymph node metastases in Adamts1 Ϫ/Ϫ mice, the infrequency of lymph node metastases of PyMT tumors (consistent with previous reports 45 ) precludes any interpretation of a role for ADAMTS1 in dissemination to lymph nodes.…”
Section: Discussionsupporting
confidence: 88%
“…Lymphangiogenesis in the ovary is dependent on ADAMTS1 activity, 3,43 and in breast cancers enhanced lymphangiogenesis provides a route for dissemination to lymph nodes and eventually metastasis to distal tissues such as lung. 44 Although we found the lowest proportion of lymph node metastases in Adamts1 Ϫ/Ϫ mice, the infrequency of lymph node metastases of PyMT tumors (consistent with previous reports 45 ) precludes any interpretation of a role for ADAMTS1 in dissemination to lymph nodes.…”
Section: Discussionsupporting
confidence: 88%
“…For example, α3β1 integrin is required for adhesion to laminin during pulmonary metastasis 100 , whereas blocking αvβ1 integrin inhibited metastasis through suppression of expression of the protease urokinase plasminogen activator (uPA) 11 . The data for αvβ1 integrin are consistent with the inhibition of metastasis associated with uPA deficiency in the MMTV-PyMT model of breast cancer 101 . Early experiments by Liotta and colleagues showed that co-injection of tumour cells with fibronectin in experimental metastasis models increased tumour cell adhesion and metastasis 102 .…”
Section: Adhesion and Invasion In The Establishment Of Metastasissupporting
confidence: 76%
“…For RA and possibly for osteoarthritis, my coinvestigators and I as well as other investigators have argued that uPA may be a therapeutic target, provided that the possible complication of persistent fibrin upon its blockade does not occur (1)(2)(3)9,24). Its inhibition may also have benefit, for example, in cancer metastasis (25), cardiac fibrosis (26), and lung inflammation (27). What is sorely needed for an understanding of the biology and pathology associated with the PA/plasmin system are potent and highly specific inhibitors of the PA activities that have the appropriate pharmacokinetics.…”
Section: Resultsmentioning
confidence: 99%